Possible Legal Cooperation for a BRICS Perspective on International and Transnational Economic Law - E. M. D. Silva; B. R. S. Campos (BRICS Law Journal, 2021)
This research paper seeks to identify and analyze the regulations that rule the economic life of the BRICS countries in the fields of foreign investment’s law, competition law and global administrative law, and further to identify points of convergence and divergence among them in order to indicate the possibilities of legal cooperation to facilitate economic exchanges and investments flow among them. We believe that the possible bottlenecks in trade and investment can be overcome mostly by exchange of experiences, to mitigate the lack of knowledge on national laws and regulations, and by the creation of cooperative mechanisms that facilitate the economic flow among them.